AGE - RELATED CATARACT RISK FACTOR - Amiri, F; Asemi, S; Mohammadi, R; Haghani, H (Iran University of Medical Sciences, 2001)
Background : Cataract is the cause of blindness in half of the cases (17 million people) over the world and increasing significantly each decade. In spite of it's role as a common health problem in different communities, man's knowledge on it's causative factors has been inadequate and various investigations have found contradictory results on that.   Objective : Risk factors determination in age- related cataract.   Design : Study was done upon case - control method Information gathering means were questionnaires which completed through an interview, in which participants were asked about his/her personal identifications, personal and health predisposing factors and family history of age- related cataract.   Samples : According to the eligibility requirement for the study, 501 people were invited and classified into two groups (247 people in age related cataract and 254 in control group).   Results : Job was found to be a personal factor for age - related cataract, while consumption, of aspirin, poultry meat and receiving electric shock were showed to be health risk factors. Other factors had no predisposing effects. According to calculated adds ratio, family history of smoking, diabet, long lasting diarrhea, usage of tranquilizers, Atenolol, Methyldopa, Triamterene- H, Nifindipin and receiving shock have increased the incidence of age- related cataract.   Conclusion : With regard to risk factors of age- related cataract, it's necessary to inform society abut protective measures and perform special protective intervention.